The World, with the Tracts & Discoveries of the Latest Navigators. - Kelly, Thomas (Thomas Kelly, 1820)
This map shows the entire world, broken down into two hemispheres (with are connected circles). The western hemisphere is shown to the left and the eastern hemisphere is to the right. Continents, some countries and major cities, and bodies of water are marked and labeled. Additionally, the routes of Captain Cook and other explorers of the late 1700s are noted and labeled.